The chair : rethinking culture, body, and design - Cranz, Galen (New York ; London : W.W. Norton, 1998)
Traces the history of the chair and provides guidelines to assist the reader in choosing a chair that suits one's body.
pt. 1. Why do we use chairs? How chairs evolved ; The elements of style -- pt. 2. What's wrong with the chair? An ergonomic perspective ; A body-mind perspective -- pt. 3. Toward body-conscious design. The chair reformed ; Beyond interior design.
Includes bibliographical references and index.
Keywords: Chair design; Chairs